1998
DOI: 10.3989/gya.1998.v49.i3-4.740
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Frying process in the relation fat/degenerative diseases. (c) Consejo Superior de Investigaciones Científicas Licencia Creative Commons 3.0 España (by-nc) http://grasasyaceites.revistas.csic.es (c) Consejo Superior de Investigaciones Científicas Licencia Creative Commons 3.0 España (by-nc) http://grasasyaceites.revistas.csic.es (c) Consejo Superior de Investigaciones Científicas Licencia Creative Commons 3.0 España (by-nc) http://grasasyaceites.revistas.csic.es (c) Consejo Superior de Investigaciones Científic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A recent review [ 8 ] reported that total frying time is normally limited to the first phase of the water cycle, evaporation, with the inner temperature of food not exceeding 100 °C. However, to our knowledge, this assumption, made 20 years before [ 9 ], was never corroborated. Other experiments with different kinds of food products indicate that the main effects on PC content rely on food cooked in oil rather than on oil itself.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…A recent review [ 8 ] reported that total frying time is normally limited to the first phase of the water cycle, evaporation, with the inner temperature of food not exceeding 100 °C. However, to our knowledge, this assumption, made 20 years before [ 9 ], was never corroborated. Other experiments with different kinds of food products indicate that the main effects on PC content rely on food cooked in oil rather than on oil itself.…”
Section: Introductionmentioning
confidence: 78%
“…Research on other vegetable molecules indicates that heating could induce a net increase in PC as a result of several mechanisms i.e., partial evaporation of moisture that increases concentration in the food matrix, migration toward media with different polarity, changes in the microstructure of vegetable tissues, breakage or softening of the rigid cell walls and other components of the vegetable cells, and the decomposition of molecules linked to fibre. A recent review [8] reported that total frying time is normally limited to the first phase of the water cycle, evaporation, with the inner temperature of food not exceeding 100 • C. However, to our knowledge, this assumption, made 20 years before [9], was never corroborated. Other experiments with different kinds of food products indicate that the main effects on PC content rely on food cooked in oil rather than on oil itself.…”
Section: Introductionmentioning
confidence: 80%
“…There is a correlation between a balanced diet and the prevention of chronic diseases, and a balanced diet also plays a critical role in maintaining health throughout the life span. [6][7][8][9] In the last two decades, the WHO Dietary Guidelines (1998) were shifted to emphasize the type of fat to be consumed and promote the ideal fatty acid profile. [5] There is no clear cutoff point for the effect of fried food consumption on human health; however, consumers should consider the risk factors related to the heavy consumption of deep-fried foods.…”
Section: Introductionmentioning
confidence: 99%
“…A formação dos compostos de degradação tais como monômeros, dímeros, polímeros e compostos cíclicos de diferentes polaridades, com ou sem oxigênio, é de grande interesse sob o ponto de vista fisiológico e nutricional, pois os compostos tornam-se parte da dieta ao permanecer dissolvidos no óleo de fritura e incorporados ao alimento frito 19 . Os possíveis riscos à saúde envolvidos no consumo de gorduras aquecidas e/ou oxidadas são predisposição à aterosclerose, ação mutagênica ou carcinogênica 9,38 .…”
Section: Introductionunclassified